Ethics in information technology - Reynolds, George Walter (Cengage, 2019)
Thorough coverage highlights notable technology developments and their impact on business. Students examine professional codes of ethics, cyberattacks and cybersecurity, security risk assessment, privacy, electronic surveillance, and freedom of expression. They also study Internet censorship, protection of intellectual property, quality software systems, IT's impact on society, social networking, and ethics of IT corporations. Unlike other introductory books with brief ethical coverage, this edition provides a thorough foundation for addressing ethical issues in the workplace -- Provided by the publisher